2007
DOI: 10.1128/jvi.02287-06
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Protein APOBEC3G Localizes to Ribonucleoprotein Complexes Found in P Bodies and Stress Granules

Abstract: Members of the APOBEC (apolipoprotein B mRNA-editing enzyme catalytic polypeptide 1-like) family of cytidine deaminases inhibit host cell genome invasion by exogenous retroviruses and endogenous retrotransposons. Because these enzymes can edit DNA or RNA and potentially mutate cellular targets, their activities are presumably regulated; for instance, APOBEC3G (A3G) recruitment into high-molecular-weight ribonucleoprotein (RNP) complexes has been shown to suppress its enzymatic activity. We used tandem affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
300
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(332 citation statements)
references
References 140 publications
(167 reference statements)
26
300
3
3
Order By: Relevance
“…TRIM5␣ cytoplasmic bodies were not observed to associate with cellular markers of actin, early endosomes, the trans-Golgi network, or lysosomes by imaging (data not shown). TRIM5␣ cytoplasmic bodies did not coincide with processing bodies (P-bodies) (Figure 2, C and D), another class of cytoplasmic body that is involved in mRNA storage and metabolism (Anderson and Kedersha, 2006) when the fluorescent P-body markers mRFP-Dcp1A ( Figure 2C) and RFP-rck/p54 ( Figure 2D) (Gallois-Montbrun et al, 2007) were expressed in HeLa cells stably expressing YFP-rhTRIM5␣. They also do not associate with vimentin as would be expected for aggresomes (data not shown) (Garcia-Mata et al, 2002).…”
Section: Examination Of Trim5␣ Localizationmentioning
confidence: 99%
See 3 more Smart Citations
“…TRIM5␣ cytoplasmic bodies were not observed to associate with cellular markers of actin, early endosomes, the trans-Golgi network, or lysosomes by imaging (data not shown). TRIM5␣ cytoplasmic bodies did not coincide with processing bodies (P-bodies) (Figure 2, C and D), another class of cytoplasmic body that is involved in mRNA storage and metabolism (Anderson and Kedersha, 2006) when the fluorescent P-body markers mRFP-Dcp1A ( Figure 2C) and RFP-rck/p54 ( Figure 2D) (Gallois-Montbrun et al, 2007) were expressed in HeLa cells stably expressing YFP-rhTRIM5␣. They also do not associate with vimentin as would be expected for aggresomes (data not shown) (Garcia-Mata et al, 2002).…”
Section: Examination Of Trim5␣ Localizationmentioning
confidence: 99%
“…Data are presented as Z-series compilations of 6 -10 images in a stack (Gallois-Montbrun et al, 2007).…”
Section: Confocal Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility was suggested immediately by subcellular localization studies, which indicated that A3G is strongly retained in the cytoplasm (Mangeat et al 2003;Muckenfuss et al 2006;OhAinle et al 2006;Wichroski et al 2006;Gallois-Montbrun et al 2007). While such sequestration would limit promiscuous editing of genomic DNA during many phases of the cell cycle, nuclear access could occur during mitosis when nuclear membranes break down.…”
Section: Assembly Into Large Rna-protein Complexes Inhibits Apobec3g mentioning
confidence: 99%